GLOBALLASIW DAWIRINDE MILLIY, REGIONALLIQ QÁDIRIYATLARDIŃ ÓZ ARA BAYLANISI - Allambergenov, A. (SCIENCE and SOCIETY, 2023)
The article examines the relationship of national ideological images from a scientific and theoretical point of view with the problems of value in the work of oriental geniuses.